Sobre las obligaciones y su clasificación - Castillo Freyre, Mario (2014)
It’s impossible to conceive the human being without the Law of Obligations. This branch ofCivil Law allows persons to satisfy their needs,reason why it’s important to study it carefully.In this article, the author presents us an introductory study of what obligations are, as well as their diverse classification. Without a doubt, this is a mandatory reading for all lawyers and Law students.